HiL Virtual System for an Industrial Process, Control and Monitoring Sulfuric Acid Production - Toaquiza Balderramo, Jaime Fernando (2023)
Virtual environments allow the incorporation of new forms of study in process control. Thus, the Hardware in the Loop takes shape in training fields. In this article, a virtual environment of the sulfuric acid production process is developed. The three-dimensional model of the system is based on a natural system that is replicated in Blender software, and the virtual system is implemented in Unity 3D to simulate its behavior. This system is developed in the Hardware in The Loop approach, in which a process is simulated, and real devices perform the control. The interaction with the outside is a Human Machine Interface; this interface allows control and monitoring. In addition, the system provides support in the learning process of an operator in the process control area because interacting with a PLC in a physical way and applying tuning methods in real control loops without running risks brings the user closer to the work environment. The main result of this project is to obtain professional training tools in the field of process control.